Phytoplankton trigger the production of cryptic metabolites in the marine actinobacterium Salinispora tropica. Issue 1 (5th December 2020) - Chhun, Audam; Sousoni, Despoina; Aguiló‐Ferretjans, Maria del Mar; Song, Lijiang; Corre, Christophe; Christie‐Oleza, Joseph A.
Summary: Filamentous members of the phylum Actinobacteria are a remarkable source of natural products with pharmaceutical potential. The discovery of novel molecules from these organisms is, however, hindered because most of the biosynthetic gene clusters (BGCs) encoding these secondary metabolites are cryptic or silent and are referred to as orphan BGCs. While co‐culture has proven to be a promising approach to unlock the biosynthetic potential of many microorganisms by activating the expression of these orphan BGCs, it still remains an underexplored technique. The marine actinobacterium Salinispora tropica, for instance, produces valuable compounds such as the anti‐cancer molecule salinosporamide but half of its putative BGCs are still orphan. Although previous studies have used marine heterotrophs to induce orphan BGCs in Salinispora, its co‐culture with marine phototrophs has yet to be investigated. Following the observation of an antimicrobial activity against a range of phytoplankton by S. tropica, we here report that the photosynthate released by photosynthetic primary producers influences its biosynthetic capacities with production of cryptic molecules and the activation of orphan BGCs. Our work, using an approach combining metabolomics and proteomics, pioneers the use of phototrophs as a promising strategy to accelerate the discovery of novel natural products from marine actinobacteria. Abstract : Interaction of Salinispora tropica with phytoplankton. Marine phototrophs release photosynthate that triggers the biosynthesis of novel cryptic metabolites in S. tropica . S. tropica produces an unknown antimicrobial molecule that kills phytoplankton.